Why Knowledge is Special. (18th January 2017) - Ryan, Shane
Abstract: I argue against Greco's account of the value of knowledge, according to which knowledge is distinctively valuable vis-à-vis that which falls short of knowledge in virtue of its status as an achievement and achievements being finally valuable. Instead, I make the case that virtuous belief is also an achievement. I argue that the nature of knowledge is such that knowledge is finally valuable in a way that virtuous belief is not, precisely because knowledge is not simply a success from ability. The value of knowledge lies in the positive responsiveness of the world to an agent's epistemic virtuousness.